WHY THE MORAL MINORITY COULD NOT BECOME A MAJORITY: OBSERVATIONS OF A PARTICIPANT-OBSERVER. - Pierard, Richard V. (Fides et historia, 2015)
The article comments on David R. Swartz's book "Moral Minority: The Evangelical Left in an Age of Conservatism." It provides a background of the Old Christian Right political faction in the U.S. and the emergence of the Evangelical Left. It also criticizes the failure of Swartz to discuss the Social Action Commission of the National Association of Evangelicals.